(untitled) (International journal of artificial intelligence, 2025)
Entrepreneurial talent or entrepreneurial personality, businessman or businessmen. The author provides information about the formation of entrepreneurial skills in students of vocational schools, improving entrepreneurial talent and the attention paid to entrepreneurship in our country.